Pengelompokan Kabupaten/Kota Berdasarkan Produksi Tanaman Pangan Sumatera Utara Tahun 2020 Menggunakan Pengelompokan Hirarki Aglomeratif - Riadhoh, Afdhah Nur; Puspita, Galuh Eka; Rafidah, Inas; Widodo, Edy (KUBIK: Jurnal Publikasi Ilmiah Matematika, 2022)
Food plants are one of the basic needs of humans as a source of energy because they contain carbohydrates and proteins that are important for the human body. North Sumatra is one of the provinces in Indonesia, known for high potential in the agricultural sector, such as food crops. However, each district/city has a very diverse amount of food crop production in North Sumatra, so it is necessary to grouping in districts/cities based on the high and low of food crop production commodities in North SumatraÂ  with the aim of assisting government in improving and optimizing government programs that engaged in agriculture. The grouping used agglomerative hierarchical cluster analysis methods, namely single linkage, average linkage, complete linkage, ward's, and centroid methods. Based on the highest cophenetic correlation value (close to 1), it was found that average linkage was the best cluster method. The results of this study that North Sumatra Province is divided into 4 clusters, consisting of regencies/cities, which can be seen from each food crop production in the very high category, the production of food crops in the high category, the production of food crops in the low category, and the production of food crops in the very low category.